VD_FINDINFO HC / 2013 / 820 vom 28. Oktober 2013 - VD Tribunal cantonal (2013)
RÉSILIATION, PROLONGATION DU BAIL À LOYER, BAIL À LOYER, LOGEMENT | 271 al. 1 CO, 271 CO, 272 al. 1 CO, 272 al. 2 CO, 272 CO, 272b al. 1 CO, 272b CO